POSTER ЯК ІНСТРУМЕНТ ЦИФРОВІЗАЦІЇ СИСТЕМИ УПРАВЛІННЯ ПІДПРИЄМСТВАМИ ГОТЕЛЬНО-РЕСТОРАННОГО БІЗНЕСУ - Fostolovych, Valentyna; Botsian, Tetiana; Pavlova, Svitlana; Fostolovych, Ruslan; Gurtovyi, Yurii (Zhytomyr Ivan Franko State University, 2024)
In the basis of the development of modern business, digital transformations have acquired primary importance. The stability of the business, and in general its ability to function, is determined by the level of digitalization. The integration of basic business development tools is considered through the prism of automation, robotics and digitization. In the field of hotel and restaurant business, digital technologies have become the most effective tool for implementing business tasks and solving problems of the control system, constant monitoring and management. The main trajectory of the automation of hospitality enterprises through the prism of the introduction of cloud technologies into business has become the use of software products. Cloud automation systems, in particular the Poster program, serve as a modern tool for accounting, control and business management. The Poster program (system) was the first cloud-based automation system developed in Ukraine to serve hotel and restaurant businesses. This software product has become a successful modern initiative, which is used with pleasure by twenty thousand hospitality establishments. When the enterprise implements this cloud technology, the approach to the organization and conduct of business has completely changed, the management system has acquired a completely new dimension. Important functions of the module have become such as: cash register for waiters with integrated hall cards; the Kitchen Kit application from Poster with a screen in the kitchen/bar, or with a system of runners; automation of the restaurant delivery service to work with orders from aggregators or personal delivery service; Poster mobile cash register; Poster QR for automatic menu creation in Poster-POS, quick payment, the possibility of tipping the waiter, leaving guest reviews, etc.; the Poster Boss app with the ability to work on a smartphone and more. The convenience of working with the Poster software is manifested in its simplicity and easy accessibility for staff training, since even intuitively, in an hour of work with this cloud technology, you can already work freely. The ability to work with cash register modules for sales and a control panel for owners makes the Poster software product both unique due to its multifunctionality and system, and easy to use. The statistics module automatically summarizes revenue data when the check is closed at the cash register. In the process of selling a finished product or service, ingredients (inventories) are written off from the warehouse according to technological maps developed by the institution.  The multifunctionality of the Poster program makes running a hotel and restaurant business more efficient, as convenient as possible in management and acts as a high-quality database for making effective management decisions. The complexity and systematicity of this cloud technology brings the innovative orientation of hospitality enterprises to a new level.